Hydrogen-bonding networks of purine derivatives and their bilayers for guest intercalation. Issue 1 (24th November 2015) - Jang, Yoona; Yoo, Seo Yeon; Gu, Hye Rin; Lee, Yu Jin; Cha, Young Shin; You, Laekyeong; Noh, Kyungkyou; Kim, Jaheon
Abstract : 6-Chloro-9-propyl-purin-2-amine (pr-GCl) forms two-dimensional hydrogen-bonded networks which in turn stack via π–π interactions, leading to the formation of bilayers that can accommodate organic guest molecules. Abstract : Two purine derivatives, 6-chloro-9-propyl-purin-2-amine (pr-GCl) and 6-chloro-9-pentyl-purin-2-amine (pt-GCl) have been synthesized and their crystal structures were determined by single crystal X-ray diffraction analyses. The purine rings in pr-GCl or pt-GCl form unique two-dimensional hydrogen-bonding networks which in turn stack via π–π interactions to give bilayers covered with alkyl chains. In pt-GCl, the pentyl groups interact effectively among themselves so that void space for guest molecules is not available. In contrast, pr-GCl can form host–guest co-crystals. Nuclear magnetic resonance (NMR) analyses of the pr-GCl crystals immersed in various solvents for up to 60 min indicate that aromatic molecules (benzene, xylene isomers) are better guests than aliphatic ones ( n -hexane, cyclohexane, isooctane) in terms of their inclusion time and amount. Powder X-ray diffraction (PXRD) patterns for the guest-included pr-GCl crystals are quite different from the simulated one, supporting the guest diffusion into the pr-GCl crystals. The crystal structure of p -xylene@pr-GCl reveals that p -xylene molecules are intercalated between the characteristic pr-GCl bilayers that are shown in both pr-GCl and pt-GCl crystals.